A Comparative Analysis of Socio-Legal and Psycho-Social Theories and the Construction of a Model to Explain How Law Operates and Evolves in the Dependency Court - Sinclair, Kate (2002)
This thesis examines data and theory about how the system of law (SL) operates and evolves: it contrasts data from social workers and attorneys working in the juvenile dependency court with theories about how individuals and social systems evolve. The analysis is based on research conducted in San Diego and revolves around a theory about human development, or the "individual as a system" (HD), and a theory about social systems, such as the autopoietic theory of law and its self-reproducing system (LA). It is suggested that together, the theories of HD+LA help to examine how professionals and law operate and evolve in the legal system. Overall, the thesis rejects the autopoietic systems theory that law reproduces itself, by itself. Instead, analysis in this study supports the finding that law is defined and operates through a dialectic of the individual and the social (or the organic and the mechanistic respectively) such that each gives rise to the other. On the basis of this system connection, aspects from systems theory about legal autopoiesis are integrated into concepts from constructive-developmental theory (HDLA), thus providing a new framework through which to examine how law and its system functions. The new framework is built around an equation that emerged some time after data analysis and theoretical development: SL=HDLA+DSA . The equation states that: The evolution of the system of law involves processes of human development and to some but a much lesser degree, the autopoietic nature of law. The extent of this evolution is best determined by analyzing data from a court setting. The dialectical relationship between individual and social influences in the evolution of law is facilitated by the accumulation of social action - such as activity from media and advocacy groups - and the individual meaning that professionals make about this action, which in turn has an influence on the formal and informal operations that they perform when operating law. The nature of these interacting dynamics will be shown through two interconnected tools of analysis: one is a typology of individual, professional and system self-concepts; the typology helps to show how a cycle of system change (human development giving rise to legal change and vice versa) occurs in the court; the other is the operative structure (or culture) of systems for law and social work in child abuse cases - which unite in court operations. These two interconnected tools help to show how the court operates and how social action (SA) for change contributes to professional and system change in the evolution of law